Mercantile circuits and mining boom in the central highlands at the end of the colonial era - Chocano, Magdalena (1983)
Cerro de Pasco has been the mining nucleus with the greatest socioeconomic influence in the central Peruvian highlands, its importance dates back to the end of the colonial era in which silver production gained a new boom and in this seat the most important yields of the area were achieved. -Peruvian (Fisher, 1977: 213-214, 222-223).